Optimization of honeycomb strength assignment for a composite energy-absorbing structure. (June 2018) - Yang, Chengxing; Xu, Ping; Yao, Shuguang; Xie, Suchao; Li, Qingming; Peng, Yong
Abstract: This study proposes a new composite structure to promote energy absorption capability of railway vehicles by integrating characteristics of a thin-walled steel structure and aluminum honeycomb fillers. Non-linear explicit code LS_DYNA3D(971) was utilized in building detailed finite element models, which were also validated by previous test data. Considering the expensive selling price, complicated fabricating technology and low production rate of high strength honeycomb, honeycombs with appropriate strength should be selected to fill in the steel structure. Therefore, scientific sampling points were chosen from the design space using Box-Behnken design method. Analysis of variance was performed in order to explore the effects of distributed honeycomb strength in four levels on crashworthiness indicators. Response surface methodology (RSM) was well applied to perform both parametric analysis and multiobjective optimization for searching the optimal configurations. Here, two different criterion were conducted in optimization process by adopting desirability approach. It was find that the composite structure with high strength honeycombs in level-1 and level-2 and relatively low strength honeycombs in level-3 and level-4 are preferable for use. Comparing with the empty steel structure, the optimal EA capacity is promoted by 35.32% in criterion 1 and 34.35% in criterion 2, being able to bear the condition with crashing speed of 36 km/h and impacting mass of 55.3 t. It illustrates that the new composite structures can be recommended as excellent crashworthy devices. Highlights: Proposes a new composite structure by integrating characteristics of thin-walled steel tubes and honeycombs to improve the crashworthiness. PRSMs were established to formulate the mathematical relationship between crashworthiness responses and honeycomb strength in four levels. Analysis of variance and parametric studies were performed to evaluate the effects of design variables on crashworthiness indicators. The desirability method with two criteria was used to seek for appropriate configurations and optimize the structural performance.